Religiosity, Guilt, Altruism and Forgiveness in Alcohol Dependence: Results of a Cross-sectional and Prospective Cohort Study. (18th April 2018) - Braun, Birgit; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd
Abstract: Aims: To compare religious denomination, religiosity, guilt, altruism and forgiveness between alcohol-dependent patients and healthy control subjects and to prospectively investigate their relationship to the disorder's 24-month course following in-patient withdrawal treatment. Method: This study in Franconia (a mainly Christian protestant region of southern Germany) applied six questionnaires to evaluate religiosity, guilt, altruism and forgiveness in 166 alcohol-dependent in-patients during withdrawal and compared findings with that of 240 healthy controls. Results: Compared to controls religious denomination was more frequently reported by the patients (OR = 1.72, P = 0.014) and patients showed higher guilt ( P < 0.001). The subjective attainability of altruism was lower in patients than in controls ( P = 0.015). Higher scores on scale of inter-religious private practice predicted earlier (Rho = −0.184, P = 0.021) and more frequent alcohol-related readmissions during the follow-up (Rho = 0.207, P = 0.009). Higher religious affiliation was related to earlier (Rho = −0.214, P = 0.008) and more frequent alcohol-related readmissions (Rho = 0189, P = 0.020). Lower values of subjective attainability of altruism predicted a worse outcome (earlier [Rho = 0.231, P = 0.003] and more frequent readmissions [Rho = −0.223, P = 0.004]). The sex-specific analyses show that some of the associations are stronger in women and others are stronger in men; however, these gender differences are small and possibly biased by multiple hypothesis testing. Conclusions: We identified religious denomination, private religious practice, religious affiliation, guilt and reduced attainability of altruism as risk factors for alcohol dependence and a worse follow-up outcome. Our findings may help to establish future preventive and therapeutic strategies.